PENGARUH PEMBERIAN KONSELING MENGGUNAKAN BOOKLET TERHADAP PENGETAHUAN DIABETES MELLITUS MASYARAKAT DI KECAMATAN ANGGANA, KALIMANTAN TIMUR - Deasy Nur Chairin Hanifa; Ika Ayu Mentari (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
Diabetes mellitus is a metabolic disease characterized by an increase in blood sugar levels due to interference with insulin secretion, insulin action or both. The aim of this research is to look the effect of counseling on public knowledge about diabetes mellitus. This research was conducted in Sidomulyo Village, Anggana District. The target of the feasibility of this research is the people who are in rural areas who mostly do not know the information about the risk, prevention, and treatment of diabetes mellitus. The method was used a counseling with booklet and the discussions. The level of knowledge was assessed using the DKQ - 24. This research used a quasi-experimental method with one group pretest-posttest design. Measurement of knowledge used Wilcoxon statistical analysis. Research respondents were dominated by 68% women and 32% of men with an age range of fewer than 60 years by 77% and more than 60 years by 23%. The results of the pretest using the DKQ-24 questionnaire showed respondents with a low knowledge category of 27%, moderate knowledge of 65%, and high knowledge of 8%. Two weeks later a post-test was conducted using the DKQ-24 questionnaire, the results obtained by respondents with the category of low knowledge by 3%, moderate knowledge by 77%, and high knowledge by 20%. The average value about the prevention and treatment of diabetes mellitus, showed pretest 10.17 ± 4.891 and posttest 14.20 ± 3.119. The relationship between pre and post counseling was found with a value of p <0,000. These results indicate the effect of increasing knowledge about diabetes mellitus after counseling.